Dinamika Transmisi Nilai: Peran Ulangan 6:4-9 dalam Pendidikan Agama Intergenerasi - Panggabean, Saut Maruli P. (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
This article examines the important function of Deuteronomy 6:4-9 in terms of intergenerational religious teaching. Using a qualitative methodology, it investigates the ways in which the principles summarized in the verse can be transmitted from one generation to the next in an increasingly diverse society. The investigation yielded new insights by showing that Deuteronomy 6:4-9 has not only theological significance but also practical application in the realm of religious education. By incorporating these teachings into educational programs, both academic institutions and families can foster an environment that is more conducive for children to understand and apply religious values in their daily lives. These insights are anticipated to offer pragmatic guidance for educators and parents in enhancing the effectiveness and relevance of religious education efforts.